Karakteristik Pembakaran Difusi Campuran Bahan Bakar Minyak Kelapa Murni Dengan Bioaditif Minyak Cengkeh - Fairuddin, Fairuddin; Riupassa, Helen; Nanlohy, Hendry Y. (Rekayasa Material, Manufaktur dan Energi, 2024)
Biofuel derived from raw vegetable oil is considered a crucial alternative energy source to address the escalating fuel energy crisis due to the growth of industrial activities and the human population. The compounds present in raw coconut oil, including saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids, and glycerol, constitute the focus of this research. The combustion of raw coconut oil involves a complex reaction due to the presence of saturated chain bonds, necessitating additional substances to weaken the carbon chains and enhance the combustion rate. This study employs the suspended droplet combustion method to increase the contact between air and fuel, thereby improving the reactivity of fuel molecules. To boost the combustion rate of coconut oil droplets, a bio-additive in the form of clove oil is experimentally added. Research findings reveal that the compound eugenol in clove oil possesses aromatic properties and a non-symmetrical carbon chain geometry. This factor can potentially expedite effective collisions among fuel molecules, consequently improving the ease of fuel combustion. In conclusion, this research provides insights into the potential use of coconut oil as a biofuel, highlighting the role of bio-additives such as clove oil in enhancing combustion rate efficiency. The study contributes to our understanding of strategies that can be applied to optimize the utilization of biofuel derived from raw vegetable oil.